2020
DOI: 10.1002/cam4.3604
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of nutritional markers in metastatic gastric and esophageal adenocarcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Patients diagnosed with advanced gastric cancer have a high mortality rate, poor prognosis following surgery, and a low survival rate 26 . However, the predictive ability of existing research and prognostic prediction models is generally limited and cannot fully reflect the patients' disease status, owing to the absence of nutritional status assessment 9–11 . Notably, TYG appears to be associated with the nutritional status of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients diagnosed with advanced gastric cancer have a high mortality rate, poor prognosis following surgery, and a low survival rate 26 . However, the predictive ability of existing research and prognostic prediction models is generally limited and cannot fully reflect the patients' disease status, owing to the absence of nutritional status assessment 9–11 . Notably, TYG appears to be associated with the nutritional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, the predictive ability of existing research and prognostic prediction models is generally limited and cannot fully reflect the patients' disease status, owing to the absence of nutritional status assessment. [9][10][11] Notably, TYG appears to be associated with the nutritional status of patients. Moreover, a previous study found that TYG is a risk factor for the development of gastric cancer in a health checkup cohort 27 ; however, research on the effect of TYG on the prognosis of patients with gastric cancer who have undergone surgery is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence further suggests that evaluate NRI at baseline and during treatment can not only indicate patients' nutrition status but also provide useful prognostic information ( 51 ). Nevertheless, while meaningful insights are procurable, little is known about the association between NRI, prognosis, and treatment efficacy in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%